Justification of a choice of methods in researches of language identity and multilingualism of youth (Eurasian Journal of Philology Science and Education, 2016)
In this article language identity and multilingualism of youth which are topical issues of modern sociolinguistics and also, methods of their researches are considered. The author notes two types of methods: active and passive. The special attention is paid to active methods which examples are testing, questioning and interview. The author provides the list of the researchers who made a big contribution to definition of methods of sociolinguistics. Achievement of productive results in sociolinguistics, as well as in other sections of linguistics is closely connected with the correct use of methods. In this regard, the author gives a complete description of questioning, as the main method used in researches of object of her work. Results of researches on a subject of work are specified in charts.
Keywords: sociolinguistics; methods of sociolinguistics; language identity of youth; multilinguism of youth; questioning